METHODS OF ATTRACTIVE CAPITAL THROUGH FINANCIAL MECHANISMS IN INTERNATIONAL FINANCIAL CENTERS - Akhmadaliyeva Nikholakhon; Omanov Khusan (Innovate Conferences, 2025)
This thesis discusses the key modalities and financing structures employed by global financial hubs to access international capital. It addresses the role of advanced stock exchanges, sovereign wealth funds, special economic zones, and high-tech fintech platforms in accessing investment. The research shows how the partnership between powerful regulatory regimes, market depth, and strategic state incentives creates a competitive landscape that channels significant capital flows into these hubs. The TIFC experience will be examined as a new model utilizing these mechanisms to integrate into the global financial system.
Keywords: Attraction of capital, financial mechanisms, international financial centers, foreign direct investment (FDI), sovereign wealth funds, fintech, special economic zones, Tashkent.